EOCENE HIGH-LATITUDE TERRESTRIAL VERTEBRATES FROM ANTARCTICA AS BIOGEOGRAPHIC EVIDENCE - Marcelo A. Reguero; Sergio F. Vizcaíno; Francisco J. Goin; Sergio A. Marenssi; Sergio N. Santillana (Asociación Paleontológica Argentina, 2015)
Abstract. A moderately diverse terrestrial biota is known from the Eocene - ?early Oligocene La Meseta Formation, Seymour Island, Antarctic Peninsula. The La Meseta Formation fills an incised valley and comprises sediments that represent deltaic, estuarine and very shallow marine environments. Forests of both deciduous and evergreen trees were dominated by Nothofagus, podocarps, and araucarian conifers. The La Meseta paleoflora is distinctive in having a predominance of Antarctic taxa; this suggests a seasonal, cold-temperate, rainy climate and a latitudinal gradient. Among the terrestrial vertebrates, there are at least nine mammal taxa, predominantly tiny marsupials (mostly endemic and new genera). The presence of these marsupials suggests the existence of some form of isolating barrier (climatic and/or geographic), which must have allowed development of this endemic fauna. Comparisons with faunas assigned to the Itaboraian (late Paleocene), Riochican (late Paleocene), Casamayoran (early Eocene), and Mustersan (tentatively assigned to the middle Eocene) ages of Patagonia were made. The assemblage of terrestrial vertebrates of the La Meseta Formation is unusual in the dominance of several endemic forms. The occurrence of protodidelphid and derorhynine marsupials, that had become extinct elsewhere in the Eocene of South America, on Seymour Island also indicates that isolation may have allowed extended survival of these taxa in the Eocene of Antarctica. The nature, distribution, and composition of the La Meseta fauna firmly suggest a latitudinal differentiation in the middle Eocene. Paleogeographic evidence suggests that the terrestrial mammals of the La Meseta Formation probably lived under crepuscular and even extended nocturnal conditions (assuming that the angle of the earth's spin axis was relatively the same as it is now) during part of the year. KEY WORDS. Antarctic Peninsula. Eocene. High latitude fauna. Mammals. Palaeobiogeography. Resumen. VERTEBRADOS EOCENOS TERRESTRES DE ALTAS LATITUDES DE ANTÁRTIDA ...